(3edJbi GdCHMQ aj aQhY GdMfajIs - (3GdMdHj, EHQGgje Hf eMeO EHQGgje, J (B956 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj habfG ddJabg aj GdOjf hHYO ajbhd EHQGgje Hf eMeO Hf EHQGgje GdMdHj bO SCdfj HYV WGdHj GdGSJaGOI Cf CLeY dg cJGHG jTJed Ydi eSGFd GdbOhQj hGdeNJGQ hGdcfR hGdhbGjI aCLHJg Edi Pdc SejJg edJbi GdCHMQs
(3BNQgG (B:s
(3Efj ROJ eSGFd cKjQI ef GdgOGjI hef eLeY GdHMQjf hde CRO TjFG ef ZjQgeG MJi jSgd GdWdH Ydi ef GTJHg Ydjg UMI TjA eeG djS aj GdcJH GdCQHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 66s
(3eYLe GdeDdajf (B1 / 55s
(3cTa GdXfhf (B2 / 1814s
(3TPQGJ GdPgH (B8 / 308s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs